Fiery words: Unveiling anger in Hindi idioms through conceptual metaphors and metonymies - Abhijeet Satsangi (نشریه پژوهش‌های زبان‌شناسی)
This paper investigates the conceptual and cognitive motivations behind anger-related Hindi idioms. The study is based on 40 idiomatic expressions on anger curated from diverse sources, including websites, books, and native speakers’ intuition. The study employs the theoretical framework of Conceptual Metaphor Theory (CMT) by Lakoff and Johnson (1980) for the analysis of these linguistic expressions. For the identification of conceptual metaphors, Metaphor Identification Procedure (MIP) by Pragglejaz Group (2007) was employed After analysis, nine conceptual metaphors and an equal number of conceptual metonymies were found in the chosen idiomatic expressions. Conceptual metaphors such as “ANGER IS FLUID,” “ANGER IS A WILD ANIMAL,” and “ANGER IS A STORM,” as well as conceptual metonymies like “REDDENING OF THE FACE” and “GNASHING OF TEETH,” were identified, among others. The findings reveal that there is a coherent conceptual organization underlying these idioms, predominantly characterized by conceptual metaphor and metonymy. The study can give us insight into the cultural conceptualisation of anger expressions in Hindi which can contribute the broader landscape of emotion research from Cognitive linguistic point of view and also in teaching-learning of Hindi idioms.